Therapeutic hypothermia for neuroprotection after off-hospital cardiac arrest: Too cool for school? - Collins, Jack (Trinity Student Medical Journal, 2010)
Approximately 5000 people in Ireland suffer an out-of-hospital cardiac arrest annually, and surprisingly, only 5.4% are expected to survive such an event. A significant number of those who do survive to hospital discharge encounter varying degrees of neurological deficit. Many studies indicate that survival and neurological outcome after suffering an out-of-hospital cardiac arrest can be improved by inducing mild hypothermia for up to 24 hours follow- ing the return of spontaneous circulation. Although the exact physiological processes underlying this intervention are not clearly understood, hypother- mia is thought to interfere with the mechanisms associated with ischaemic and reperfusion injury. Several methods to induce therapeutic hypothermia have been developed and include external cooling, intravascular cooling and combinations of both. Clinical trials examining the safety of therapeutic hy- pothermia suggest it presents little risk to patients. However, these studies have inherent limitations in their research methodology. A number of inter- national surveys of physicians suggest that this treatment is underutilised due to a lack of both published data on its safety profile and the absence of local protocols. The use of therapeutic hypothermia in Ireland is yet to be analysed and there is little published data available on Irish out-of-hospital cardiac arrest survival.